Kesiapan Pelaksanaan Rekam Medis Elektronik (RME) dengan Pendekatan 5 M (Man, Money, Material, Machine, Methode): Studi Kasus RSUM Ponorogo - Ria Fajar Nurhastuti (Pusat Riset dan Inovasi Nasional, 2025)
Electronic Medical Record (EMR) is a system used to record medical information of patients electronically, which aims to facilitate and speed up the recording process. The use of EMR offers ease, practicality, and efficiency in patient data management (Yoga et al., 2020). This study aims to analyze the readiness of implementing EMR at the Muhammadiyah General Hospital in Ponorogo, based on the 5M management elements (Man, Money, Material, Machine, Method). The study uses a descriptive qualitative design with a case study approach, which was conducted through interviews to obtain data. The sample in this study consisted of 27 healthcare workers involved in using the EMR application. The sample was selected using purposive sampling. The results showed that the readiness of EMR implementation in terms of the Man element (human resources) is quite good, as most of the staff have demonstrated readiness in using the EMR application, as seen from their comfort and skills in operating the system. In terms of Money, the hospital has allocated sufficient funds for the maintenance of the EMR system, which is continuously updated, and for its implementation in the inpatient and Emergency Department (ED) areas. For the Material element, the software used for EMR is adequate and ready to support the implementation of the system. In the Machine element, the availability of computers and supporting devices, such as stable internet connections and servers, has been well established. The user-friendly system also supports the implementation process. Finally, the Method element shows that there are clear SOPs (Standard Operating Procedures) for EMR implementation and workflows that are easy to follow by the users. Overall, this study indicates that the Muhammadiyah General Hospital in Ponorogo is ready to implement the Electronic Medical Record system with strong support in all 5M management aspects.